2011
DOI: 10.1083/jcb.201107093
|View full text |Cite
|
Sign up to set email alerts
|

Stress-responsive maturation of Clk1/4 pre-mRNAs promotes phosphorylation of SR splicing factor

Abstract: A nuclear pool of partially spliced Clk1/4 pre-mRNAs matures in response to stress and induces SR protein phosphorylation and activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
171
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(181 citation statements)
references
References 52 publications
10
171
0
Order By: Relevance
“…It will be interesting to examine whether pools of completed but unspliced transcripts can be differentially spliced depending on cellular conditions. It has been shown that a pool of partially spliced Clk1/4 mRNA is stored for later completion in response to stress, but this RNA does not appear to be at the Clk1/4 locus (Ninomiya et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to examine whether pools of completed but unspliced transcripts can be differentially spliced depending on cellular conditions. It has been shown that a pool of partially spliced Clk1/4 mRNA is stored for later completion in response to stress, but this RNA does not appear to be at the Clk1/4 locus (Ninomiya et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Transcripts encoding the SR protein kinase Clk1 were previously shown to accumulate in the nucleus, fully spliced except for two introns; these introns were rapidly spliced to produce coding mRNA in response to heat or osmotic shock as well as upon inhibition of Clk kinase activity by a smallmolecule inhibitor (Ninomiya et al 2011). Clk kinase activity thus appears to promote the detention of these introns by inhibiting their splicing.…”
Section: Properties Of Dismentioning
confidence: 99%
“…adenylated pre-mRNAs encoding the SR protein kinase Clk1 contain two unspliced introns flanking a cassette exon. These intron-containing transcripts are retained in the nucleus until the cells experience heat or osmotic shock or treatment with a chemical inhibitor of the Clk kinases, at which point splicing occurs, allowing production of more protein (Ninomiya et al 2011). Intriguingly, Clk kinases are also implicated in the control of splicing of retained introns in platelets.…”
mentioning
confidence: 99%
“…The skipped exon 4 and intron retention variants are either both inactive or rapidly cleared by nonsense-mediated decay (63,69). The loss of CLK1 activity may disrupt a feedback loop because its kinase activity is critical for the phosphorylation of multiple SR proteins that regulate splicing (63,70,71). The inclusion of CASP3 exon 2 with EWS-FLI1 reduction places an internal ribosome entry site into the 5′-UTR of the mRNA (72).…”
Section: Yk-4-279 Alters Splicing Rather Than Direct Transcriptionalmentioning
confidence: 99%
“…One prior report identified EWS-FLI1 increasing TERT activity independently of DNA binding; however, no isoform analysis was performed (56). These four genes were recognized as putative contributors to oncogenesis based on the published literature (57)(58)(59)(60)(61)(62)(63)(64)(65). None of these genes were alternatively spliced by WT EWS reduction.…”
Section: Yk-4-279 Alters Splicing Rather Than Direct Transcriptionalmentioning
confidence: 99%